PENATALAKSANAAN FISIOTERAPI PADA PASIEN POST REKONSTRUKSI ANTERIOR CRUCIATE LIGAMENT (ACL) SINISTRA DI KLINIK BINTANG PHYSIO BANDUNG : A CASE STUDY: PHYSIOTHERAPY MANAGEMENT IN POST ANTERIOR CRUCIATE LIGAMENT (ACL) RECONSTRUCTION PATIENT AT BINTANG PHYSIO CLINIC BANDUNG: A CASE STUDY - Nur Afiyati; Hani Irfana Faiza; Muhammad Ghilang Maulud Setyawan; Ardhia Pramesti Amalia (JURNAL PROFESIONAL FISIOTERAPI, 2026)
Introduction: Anterior cruciate ligament (ACL) injury is one of the most common knee injuries and may result in instability and functional impairment, particularly in physically active individuals. In cases of ACL rupture, reconstruction surgery is performed to restore knee stability. However, during the early rehabilitation phases (phase 1–2), patients commonly experience problems such as limited range of motion and decreased muscle strength, which may hinder the process of returning to sport. Methods: This study used a case study design with a descriptive observational approach involving one post-ACL reconstruction patient at Bintang Physio Clinic Bandung. Physiotherapy interventions were administered over four sessions and included Transcutaneous Electrical Nerve Stimulation (TENS) and progressive exercise therapy. Outcome measures included range of motion assessed with a goniometer, muscle atrophy assessed by midline measurement, muscle strength assessed using Manual Muscle Testing (MMT), and functional activity assessed using the Lower Extremity Functional Scale (LEFS). Results: After four therapy sessions, the patient demonstrated improvements in range of motion from 100° to 130°, muscle strength from grade 4 to 4+, reduction in muscle atrophy, and improvement in LEFS score from 33 to 56. Conclusion: Physiotherapy intervention during the early phase after ACL reconstruction showed positive outcomes in improving knee function and functional activity, and may serve as an important foundation in preparing patients for a safe and gradual return to sport. Keywords: ACL Injury, ACL Reconstruction, Physiotherapy, Return to Sport